Experiences during Design, Fabrication, Assembly and Factory Acceptance Test of the ITER Cryoplant Termination Cold Box. Issue 1 (March 2020) - Patel, P; Vaghela, H; Muralidhara, S; Shukla, V; Garg, A; Das, J; Dash, B; Madeenavalli, S; Chang, H-S; Grillot, D; Sarkar, B; Cursan, M; et al.
Abstract: The ITER Cryodistribution (CD) system distributes cryogenic power from the cryoplant to the applications, namely superconducting magnets, cryopumps, etc. The ITER CD system comprises seven cold boxes of which the Cryoplant Termination Cold Box (CTCB) is the largest one. The CTCB plays a pivotal role in distributing the cold helium fluid with the highest mass flow rates of 4 kg/s coming from one of the 80 K plants to the applications. The physical connection between the CTCB and different applications is through nine cryolines (CLs) having diameters ranging from 0.45 m to 1.0 m. The CTCB has been manufactured and assembled with various large size components such as electrical heater system of 600 kW capacity, cryogenic control valves of size DN200, bubble panel thermal shield (TS) made of stainless steel, etc. The CTCB, which withstands interface loads of ∼1.4 times of its own weight, has been analysed for its functional and thermo-structural requirements under various load conditions. Components & subsystems were manufactured and factory tested individually in various locations in Europe and India to be finally assembled in one place. The CTCB has also been integrally tested, of which major activities were the pressure and helium leak tightness tests, followed by functionality checks of all instruments. The present paper describes the challenges involved and how they were resolved as well as lesson learnt during the design, fabrication, assembly, and factory acceptance test (FAT) phase of the CTCB project.